TSUNAMI ACEH 2004 SEBAGAI DASAR PENATAAN RUANG KOTA MEULABOH - wisyanto, wisyanto (Jurnal Sains dan Teknologi Indonesia, 2011)
Tsunami which was generated by the 2004 Aceh eartquake has beenhaunting our life. The building damage due to the tsunami could be seenthroughout Meulaboh Coastal Area. Appearing of the physical loss wasclose to our fault. It was caused by the use dan plan of the land withoutconsidering a tsunami disaster threat. Learning from that event, we haveconducted a research on the pattern of damage that caused by the 2004tsunami. Based on the analysis of tsunami hazard intensity and thepattern of building damage, it has been made a landuse planning whichbased on tsunami mitigation for Meulaboh. Tsunami mitigation-based ofMeulaboh landuse planning was made by intergrating some aspects, suchas tsunami protection using pandanus greenbelt, embankment along withhigh plants and also arranging the direction of roads and setting of building forming a rhombus-shaped. The rhombus-shaped of setting of the road and building would reduce the impact of tsunamic wave. It is expected that these all comprehensive landuse planning will minimize potential losses in the future .